A Comparison of Top Distributed Bragg Reflector for 1300 nm Vertical Cavity Semiconductor Optical Amplifiers Based on III–V Compound - Abubaker, Shawbo A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
In this work, the design of GaAs/AlGaAs distributed Bragg reflector (DBR) has been implemented for 1300 nm vertical cavity semiconductor optical amplifiers (VCSOAs) for optical fiber communication applications. The top DBR period and Al concentration are varied, the peak reflectivity of the DBR is increasing from 50% to 97.5% for 13 periods with increasing Al concentration, whereas the reflectivity bandwidth is increased to almost 190 nm. The relation between wavelength and incidence angle variation on DBR reflectivity is increasing with the incident angle (0°, 20°, 30°, and 50°), the resonant wavelength and bandwidth of the measured reflectance spectra shifts to shorter wavelength and wider bandwidth, respectively. In addition, a comparison between the linear, the graded, and the parabolic DBRs has been achieved with transfer matrix method using MATLAB software to show the influence of layer in DBRs and its effect on lasing wavelength. It is shown that using grading DBR mirror is much more beneficial compared to abrupt DBR, whereas it has lower reflectivity of almost 10% due to VCSOAs device which needs less number of top layers until prevent reaching lasing threshold.